Rheological Studies of Texture-Modified Chicken Rendang with Tapioca and Sago Starches as Food Thickener for Patients with Dysphagia - Syahariza, Z. A; Nuraihan, A.Z; Norziah, M.H; Fazilah, A (Journal of Food Technology Research, 2016)
Dysphagia refers to the term of having difficulty in swallowing or moving foods and liquids from the mouth to the stomach, which will lead to dehydration and malnutrition. Texture modified food is one of common method used in dysphagia management, by altering the rate of food travelling down the pharynx. In this study, texture modified chicken rendang was developed to comply Texture C (fine puree with lump free) as outline by Australian dysphagia standard. Rendang, one of popular traditional dish in Malaysia was selected; aim to introduce high protein diet in patient with dysphagia problem. Texture modification was carried out by adding commercial thickener, and later was compared to formulation with addition of tapioca and sago starch as the thickener. Effect of using different types of food thickener, together with different level of starch addition and serving temperature on the rheological properties of developed food were investigated. Results showed that all thickened samples demonstrated a shear thinning effect throughout the temperature studied, contributed by starch integrity loss due to heating. Both storage modulus (G’) and loss modulus (G") values of samples containing starch decreases as temperature increases, indicating a weak gel like properties associated with each sample. The addition of 5% of starch was found to be optimal for the sample to remain stable even at 85°C. Tapioca starch could potentially use as cheaper thickener alternative due to its stable structure upon oscillation frequency and temperature increment during rheological analysis, when to compared to sago starch. Introduction of chicken rendang puree, thickened with starch potentially help to provide safer food for patients with dysphagia.